Direito fundamental à autodeterminação informativa e a proteção da personalidade nos contratos eletrônicos - Couto, José Henrique de Oliveira (2024)
In surveillance capitalism, personal data are assets that drive the economy, contributing to the development of products and services, business decision-making and marketing creation. Thus, private life has become the "air we breathe" due to its essentiality. The electronic consumer contract has accelerated the process of the digital personality economy because its code facilitates the manipulation of privacy and enables data processing at an almost absolute level. In addition to clauses with difficult terms and small print, the click-wrap of the electronic contract gives the entrepreneur the presumption that the consumer has agreed to all contractual rules – even if, as a rule, the data subject does not even know that the data will be processed or what the processing will be, the time, the purpose and those responsible. This context contributes to the personality economy, exposing data subjects to the risks of discriminatory or illicit processing that can impact the free development of the personality and the protection of the electronic body, especially when it involves health, sexual, financial and religious data. Based on this, it is necessary to adapt the source code of transactions concluded on the Internet to allow the effective exercise of consent to limit the processing of personal data, applying the logic that it is up to the consumer, not third parties, to control his or her private life. In this context, informational self-determination becomes a fundamental right because it grants autonomy to the data subject, who can then limit the management of his or her private life and make choices that do not cause harm to his or her personality, such as preventing sensitive data from being processed (without any relation to the purpose of the transaction). It is worth noting that this research, which uses the hypothetical-deductive methodology, has as its primary objective to demonstrate that informational self-determination is a fundamental right because it protects the electronic personality and personal data of consumers who contract on the Internet. In the construction of this work, bibliographical studies were collected, in addition to using case law and legal standards.